Analisis Efektivitas Prosedur Penyelesaian Kepailitan dalam Perspektif Hukum Perdata: Studi Putusan Nomor 47/Pdt.Sus-PKPU/2022/PN Niaga Sby dan Nomor 48/Pdt.Sus-PKPU/2022/PN Niaga Sby - Piter, Ryanto; Moh. Yuda Sudawan (LPPM Universitas Ekasakti Padang, 2024)
Bankruptcy and Postponement of Debt Payment Obligations are crucial legal mechanisms in the Indonesian civil law system for dealing with insolvency and debt restructuring of debtors. This study analyzes two Commercial Court decisions at the Surabaya District Court, namely Decision Number 47/Pdt.Sus-PKPU/2022/PN Niaga Sby and Decision Number 48/Pdt.Sus-PKPU/2022/PN Niaga Sby, in order to evaluate the effectiveness of bankruptcy procedures. civil law perspective. This analysis includes a review of regulations, theory and implementation of bankruptcy procedures and their implications for creditors and debtors. The research method used is normative juridical analysis based on court decisions and relevant literature. The research results show that, in a legal context, Articles 21 to 64 of the UUK-PKPU regulate the consequences of bankruptcy using two implementation methods, namely by law and rule of reason. An evaluation of two Commercial Court decisions in Surabaya shows the importance of protecting creditor rights in the bankruptcy process. The curator plays a key role in ensuring creditors receive fair payments from the liquidation of debtor assets. These two decisions emphasize the application of the pari passu prorata parte principle, the creditorium principle, and the business continuity principle to maintain a balance between creditor rights and debtor business continuity.